Support for global health and pandemic preparedness in medical education in Germany: Students as change agents. (11th March 2021) - Kreitlow, Annika; Steffens, Sandra; Jablonka, Alexandra; Kuhlmann, Ellen
Abstract: The COVID‐19 pandemic has reinforced Germany's role as global health player, but the education system is lagging behind and does not adequately prepare health professionals for the new challenges. This study aims to strengthen global health in undergraduate medical education in Germany. Major objectives include: to review the current situation, explore changing demand for global health and introduce innovative teaching models and the drivers for change. Mixed methods and an explorative approach were applied, comprising a scoping review, online surveys carried out at Hanover Medical School, March/April 2020. Target groups were undergraduate medical students ( n  = 384) and additionally lecturers ( n  = 172), and finally new multiprofessional teaching courses initiated by students and developed collaboratively. The results reveal only slow pace of change on the level of the education system, while demand for global health education has increased markedly in all actor groups, but strongest in the group of students in the preclinical phase. Implementation of global health programmes illustrates how students can become change agents and enhance institutional innovation bottom‐up. However, in order to achieve wider transformative potential, these efforts must be flanked by macro‐level policy changes and integrated in future pandemic preparedness strategies.